Rhodium-Catalyzed Ortho-Vinylation of 2-Arylpyridines and Its Application in the Total Synthesis of Palmatine - Shan Lv; Ruifang Nie; Lingmei Guo; Yang Zheng; Yanzhao Liu; Li Guo; Yong Wu (Georg Thieme Verlag KG, 2020)
An efficient protocol by Rh-catalyzed direct C-H vinylation of 2-arylpyridines with a commercially available and air-stable potassium vinyl donor has been developed. This method affords the corresponding pyridinyl styrene derivative with moderate to excellent yields under mild conditions, which is extremely beneficial to the total synthesis of the natural product palmatine.